Billie Holiday - Kliment, Bud. (Philadelphia : Chelsea House, 1990)
A biography of the American jazz singer whose life was changed by drug abuse and alcoholism.
Includes bibliographical references (p. 108) and index.
Booklist.
School Library Journal.
Wilson's Junior High School.
7.1
5-8
Keywords: Holiday, Billie, -- 1915-1959 -- Juvenile literature; Holiday, Billie, -- 1915-1959.; Holiday, Billie, -- 1915-1959.; Singers -- United States -- Biography -- Juvenile literature; African Americans -- Biography; Singers; African Americans -- Biography; Singers -- Biography